IDENTIFIKASI SEKTOR EKONOMI UNGGULAN PADA PROVINSI RIAU - Yosef Felix Sitorus; Dani Rahmad Setiawan; Fikri Dias Basmallah; Amin Prawiro Madani; Muhammad Refkhi Al Aqilah; Prayoga Setiawan (Lembaga Pengembangan Kinerja Dosen, 2025)
Regional economic growth can be studied from various points of view, one of which is based on business sectors that produce economic products. This research aims to analyze business sectors in Riau Province with a quantitative descriptive test approach by using data from 2015 to 2022’s Gross Regional Domestic Product based on constant prices. The analysis methods are Location Quotient, Dynamic Location Quotient, Shift Share, and Klassen Typology. The research analyzed 52 business sectors classified by the Indonesian Central Bureau of Statistics. The results of this research show that the business sectors in Riau Province with good analytical results based on all the analysis methods are plantation crops, agricultural and hunting services, forestry and logging, coal and oil and gas refining industries, and paper and paper products industries; printing and reproduction of recorded media. The relevant government can prioritize these sectors while still considering other aspects to increase economic growth in Riau Province.